2022
DOI: 10.3390/ijms23158178
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of Insulin and Hypothalamic-Pituitary-Adrenal (HPA) Axis in the Metabolic Syndrome

Abstract: Recent data suggests that (pre)diabetes onset is preceded by a period of hyperinsulinemia. Consumption of the “modern” Western diet, over-nutrition, genetic background, decreased hepatic insulin clearance, and fetal/metabolic programming may increase insulin secretion, thereby causing chronic hyperinsulinemia. Hyperinsulinemia is an important etiological factor in the development of metabolic syndrome, type 2 diabetes, cardiovascular disease, polycystic ovarian syndrome, and Alzheimer’s disease. Recent data su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 126 publications
2
16
0
2
Order By: Relevance
“…Correspondingly the study by Elhassan et al found cortisol levels in young children to be affected by earlier exposure to maternal pregnancy weight gain but not maternal pre‐pregnancy BMI (Elhassan et al, 2015). It could be speculated that the reason behind this could be that excessive weight gain in pregnancy causes hyperinsulinemia and in this way introduces an increased activation of the HPA axis (Anagnostis et al, 2009; Janssen, 2022; Miranda et al, 2016) in contrast to a potential flatting of the cortisol curve in pregnancies with a continues exposure to obesity before and during pregnancy. It should also be noted that to get at an overall understanding of the cortisol transport and metabolism several other types of transport and extrusion proteins involved in cortisol transport should also be taken into account, especially the glucocorticosteroid eliminating enzyme cytochrome P450 CYP3A4 (van Keulen et al, 2020) and placental p‐glycoprotein (Ge et al, 2021; Lye et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly the study by Elhassan et al found cortisol levels in young children to be affected by earlier exposure to maternal pregnancy weight gain but not maternal pre‐pregnancy BMI (Elhassan et al, 2015). It could be speculated that the reason behind this could be that excessive weight gain in pregnancy causes hyperinsulinemia and in this way introduces an increased activation of the HPA axis (Anagnostis et al, 2009; Janssen, 2022; Miranda et al, 2016) in contrast to a potential flatting of the cortisol curve in pregnancies with a continues exposure to obesity before and during pregnancy. It should also be noted that to get at an overall understanding of the cortisol transport and metabolism several other types of transport and extrusion proteins involved in cortisol transport should also be taken into account, especially the glucocorticosteroid eliminating enzyme cytochrome P450 CYP3A4 (van Keulen et al, 2020) and placental p‐glycoprotein (Ge et al, 2021; Lye et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamus, a crucial regulator of appetite, energy expenditure, and glucose homeostasis, has been implicated in the pathogenesis of metabolic diseases, such as obesity and type 2 diabetes mellitus [26]. As mentioned above, hormones like leptin, as well as other adipokines, play a critical role in regulating the functions of the hypothalamus.…”
Section: The Hypothalamus In Metabolic Diseasesmentioning
confidence: 99%
“…As mentioned above, hormones like leptin, as well as other adipokines, play a critical role in regulating the functions of the hypothalamus. In addition to altered hormone levels, chronic inflammation, gliosis, and endoplasmic reticulum stress can affect the hypothalamic function in metabolic diseases, leading to insulin resistance and metabolism dysfunction [26]. The alterations of cortisol and insulin concentrations can impact the progression of metabolic diseases through their effects on hypothalamic neuropeptide Y (NPY) [26].…”
Section: The Hypothalamus In Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin has direct stimulatory effects on the hypothalamussecreting GnRH while promoting oogenesis and ovulation in the 67,68 In the adrenals, insulin stimulates steroidogenesis steroidogenesis factor 1 establishing its direct involvement in regulating adrenal gland hormones. 69 Further, it is postulated that hyperinsulinaemia during PCOS can release free IGF-1 into circulation by inhibiting IGFBP-1 production in the ovaries thereby encouraging LH-stimulated androgen production. 70 Hence, in vitro and in vivo studies suggest stimulatory roles for insulin on reproduction that have been illustrated in Figure 3.…”
Section: Infertilitymentioning
confidence: 99%